If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d(d + -2) = -7 Reorder the terms: 2d(-2 + d) = -7 (-2 * 2d + d * 2d) = -7 (-4d + 2d2) = -7 Solving -4d + 2d2 = -7 Solving for variable 'd'. Reorder the terms: 7 + -4d + 2d2 = -7 + 7 Combine like terms: -7 + 7 = 0 7 + -4d + 2d2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 3.5 + -2d + d2 = 0 Move the constant term to the right: Add '-3.5' to each side of the equation. 3.5 + -2d + -3.5 + d2 = 0 + -3.5 Reorder the terms: 3.5 + -3.5 + -2d + d2 = 0 + -3.5 Combine like terms: 3.5 + -3.5 = 0.0 0.0 + -2d + d2 = 0 + -3.5 -2d + d2 = 0 + -3.5 Combine like terms: 0 + -3.5 = -3.5 -2d + d2 = -3.5 The d term is -2d. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2d + 1 + d2 = -3.5 + 1 Reorder the terms: 1 + -2d + d2 = -3.5 + 1 Combine like terms: -3.5 + 1 = -2.5 1 + -2d + d2 = -2.5 Factor a perfect square on the left side: (d + -1)(d + -1) = -2.5 Can't calculate square root of the right side. The solution to this equation could not be determined.
| x^2-3x-108= | | 38-(2c+4)=4(c+5)c | | 3x=-5x-8 | | 9x-2(3x+1)=x+1 | | -3=-9x-3 | | .09x^2-2.007x+.00012=0 | | 4(x-2)=3(x-2) | | 1/4(x-8)+7 | | x-32=-27 | | 2x-4y=12fory | | 2r+-6r=12 | | Ym+3=n | | -3m+4m-2=m-2 | | 5m+7.75=40.25 | | 5(h-1)=2(h-4)-6 | | 7/8*16 | | -6w+4=-2(3w-2) | | x/9+x=5/8 | | 8(12-y)+4y=12y-96 | | -3+2/3=4 | | 18-r=48 | | 12k+11(3k-5)= | | -9y-7=-4y-12 | | 3y-y=14 | | g-16= | | x*x=7.5*7.5+(x-1)*(x-1) | | 5y-2=15 | | t-30=14-3t | | 3(2x+2)=10x+1-4x+5 | | -x^2-.18x+.045=0 | | 6x+14=2x-6 | | 2x-2=14x+4 |